Diclofenac Sodium Treatment Ameliorates Extrapancreatic Organ Injuries in a Murine Model of Acute Pancreatitis Induced by Caerulein - Ozlem Ozer Cakir; Siddika Findik (Gastroenterology Research and Practice)
Aim. We determined the effects of diclofenac sodium, octreotide, and their combination on extrapancreatic organ injuries in caerulein-induced acute pancreatitis in mice. Methods. A total of 58 BALB-C male mice (25 g) were divided into seven groups and used to create a caerulein-induced acute pancreatitis model. Diclofenac sodium, octreotide, and their combination were given for treatment of caerulin-induced acute pancreatitis in mice. At the end of the experiment, the lung, liver, kidney, and stomach were removed for histopathologic assessment. Results. Histopathologic investigation revealed a statistically significant difference between the groups in mean congestion, edema, tubular injury, perirenal fat tissue inflammation, and tubular stasis scores in kidney tissue (P<0.001, P<0.001, P<0.001, P<0.001, and P=0.048, respectively); mean congestion, edema, neutrophil inflammation, mononuclear inflammation, and emphysematous change scores in the lung (P<0.001, P<0.001, P<0.001, P=0.030, and P<0.001, respectively); mean congestion, edema, and neutrophil inflammation scores in the stomach (P=0.008, P=0.014, and P<0.001, respectively); and mean congestion and hydropic degeneration scores in the liver (P=0.029 and P=0.002, respectively). Conclusion. Diclofenac sodium alone ameliorates lung edema due to caerulin-induced acute pancreatitis.